Alveolar ridge rehabilitation to increase full denture retention and stability - Mefina Kuntjoro; Rostiny Rostiny; Wahjuni Widajati (Dental Journal (Majalah Kedokteran Gigi), 2010)
Background: Atrophic mandibular alveolar ridge generally complicates prostetic restoration expecially full denture. Low residual alveolar ridge and basal seat can cause unstable denture, permanent ulcer, pain, neuralgia, and mastication difficulty. Pre-proshetic surgery is needed to improve denture retention and stability. Augmentation is a major surgery to increase vertical height of the atrophic mandible while vestibuloplasty is aimed to increase the denture bearing area. Purpose: The augmentation and vestibuloplasty was aimed to provide stability and retentive denture atrophic mandibular alveolar ridge. Case: A 65 years old woman patient complained about uncomfortable denture. Clinical evaluate showed flat ridge in the anterior mandible, flabby tissue and candidiasis, while residual ridge height was classified into class IV. Case management: Augmentation using autograph was conducted as the mandible vertical height is less than 15 mm. Autograph was used to achieve better bone quantity and quality. Separated alveolar ridge was conducted from left to right canine region and was elevated 0.5 mm from the previous position to get new ridge in the anterior region. The separated alveolar ridge was fixated by using T-plate and ligature wire. Three months after augmentation fixation appliances was removed vestibuloplasty was performed to increase denture bearing area that can make a stable and retentive denture. Conclusion: Augmentation and vestibuloplasty can improve flat ridge to become prominent.Latar belakang: Ridge mandibula yang atrofi pada umumnya mempersulit pembuatan restorasi prostetik terutama gigi tiruan lengkap (GTL). Residual alveolar ridge dan basal seat yang rendah menyebabkan gigi tiruan menjadi tidak stabil, menimbulkan ulser permanen, nyeri, neuralgia, dan kesulitan mengunyah. Tujuan: Augmentasi dan vestibuloplasti pada ridge mandibula yang atrofi dilakukan untuk menciptakan gigi tiruan yang stabil dan retentive. Kasus: Pasien wanita usia 65 tahun datang dengan keluhan gigi tiruan yang tidak nyaman. Pemeriksaan klinis menunjukkan ridge flat pada anterior mandibula, jaringan flabby dan kandidiasis, sedangkan residual ridge digolongkan menjadi kelas IV. Tatalaksana kasus: Augmentasi dilakukan karena ketinggian vertikal mandibula kurang dari 15 mm. Autograf digunakan untuk mendapatkan kuantitas dan kualitas tulang yang lebih baik. Alveolar ridge diambil dari sisi kiri dan kanan region kaninus dan digunakan 0,5 mm dari posisi awalnya untuk mendapatkan ridge baru pada region anterior. Alveolar ridge telah diseparasi difiksasi menggunakan T-plate dan ligature kawat. Tiga bulan setelah fiksasi dilepas, dilakukan vestibuloplasti untuk meningkatkan denture bearing area sehingga gigi tiruan lebih stabil dan retentive. Kesimpulan: Augmentasi dan vestibuloplasti dapat memperbaiki ridge atrofi sehingga menjadi tinggi kembali.